2013
DOI: 10.14257/ijhit.2013.6.5.17
|View full text |Cite
|
Sign up to set email alerts
|

Biogeography Based Optimization Approach for Solving Optimal Power Flow Problem

Abstract: This paper presents the use of a novel evolutionary algorithm called Biogeography-based optimization (BBO)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…The results of this comparison, which are given in Table , indicate that the proposed approach is superior to those reported in the literature for the same test system. Stochastic fractal search has achieved 0.229% and 0.045% less emission level reduction than those obtained using of BBO and ABC, respectively. Case: Minimization of both generating cost and emission level …”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…The results of this comparison, which are given in Table , indicate that the proposed approach is superior to those reported in the literature for the same test system. Stochastic fractal search has achieved 0.229% and 0.045% less emission level reduction than those obtained using of BBO and ABC, respectively. Case: Minimization of both generating cost and emission level …”
Section: Resultsmentioning
confidence: 87%
“…The optimal setting values of control parameter of the emission index minimization are given in Table . The results attained from the proposed SFS algorithm have been compared with other 2 methods in the literature . The results of this comparison, which are given in Table , indicate that the proposed approach is superior to those reported in the literature for the same test system.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…However, from the literature, it can be concluded that, these techniques could not solve the complex objective functions which are not differentiable, mostly with complicated constraints. To solve these, many evolutionary algorithms have been proposed and implemented in the field of power system to solve different OPF problems, such as genetic algorithm (GA) [8][9][10], particle swarm optimization (PSO) [11][12][13], artificial bee colony (ABC) algorithm [14][15], harmony search algorithm (HSA) [16][17]26], differential evolution (DE) [18][19], biogeography based optimization (BBO) [20][21][22][23], bacterial swarm algorithm (BSA) [24], modified shuffle frog leaping algorithm (MSLFA) [25], gravitational search algorithm (GSA) [27][28] etc. ABC method was employed by Adaryani et al [14] to solve the OPF problem considering both equality and inequality constraints in an electric power system.…”
Section: Introductionmentioning
confidence: 99%